Clinical significance of radiological patterns of HRCT and their association with macrophage activation in dermatomyositis. (17th February 2020) - Zuo, Yu; Ye, Lifang; Liu, Min; Li, Shanshan; Liu, Weifang; Chen, Fang; Lu, Xin; Gordon, Patrick; Wang, Guochun; Shu, Xiaoming
Abstract: Objectives: To evaluate the distribution of radiological characteristics stratified by different myositis-specific autoantibodies, identify prognostic value of high-resolution CT (HRCT) patterns in DM-associated interstitial lung disease (DM-ILD), and explore the possible mechanism associated with macrophage activation. Methods: We enrolled 165 patients with PM/DM-ILD. The distribution of HRCT radiological types with different myositis-specific autoantibodies and the relationship between radiological features and ILD course and prognosis were analysed. Additionally, the potential role of macrophage activation in rapidly progressive ILD (RP-ILD) with DM was studied. Results: The organizing pneumonia pattern was dominant in HRCT findings of patients with DM-ILD, especially those with anti-SAE (6/6, 100%) and anti-MDA5 (46/62, 74.2%) antibodies. The ratios of organizing pneumonia and nonspecific interstitial pneumonia patterns were almost equal in patients with aminoacyl tRNA synthetase antibodies, and nonspecific interstitial pneumonia pattern was associated with a mild clinical course. Lower lung zone consolidation in HRCT was related to RP-ILD in both anti-MDA5 and anti-aminoacyl tRNA synthetase antibody-positive groups. Ferritin levels of >1000 ng/ml (odds ratio (OR), 12.3; P= 0.009), elevated carcinoembryonic antigen (OR, 5.8; P= 0.046) and carbohydrate antigen 19–9 (OR, 7.8; P= 0.018) were independent predictors of a lower lung zone consolidation pattern in anti-MDA5 antibody-positive DM. The infiltration of CD163-positive macrophages into alveolar spaces was significantly higher in the DM-RP-ILD group than in the chronic DM-ILD group. Conclusion: HRCT patterns are different among variable myositis-specific autoantibodies positive patients with ILD and lower zone consolidation in HRCT correlated with RP-ILD in DM. Activated macrophages may contribute to the pathogenesis of RP-ILD in DM.